Optical secret sharing with cascaded metasurface holography - Georgi, Philip; Wei, Qunshuo; Sain, Basudeb; Schlickriede, Christian; Wang, Yongtian; Huang, Lingling; Zentgraf, Thomas (Science Advances)
Secret sharing is a well-established cryptographic primitive for storing highly sensitive information like encryption keys for encoded data. It describes the problem of splitting a secret into different shares, without revealing any information to its shareholders. Here, we demonstrate an all-optical solution for secret sharing based on metasurface holography. In our concept, metasurface holograms are used as spatially separable shares that carry encrypted messages in the form of holographic images. Two of these shares can be recombined by bringing them close together. Light passing through this stack of metasurfaces accumulates the phase shift of both holograms and optically reconstructs the secret with high fidelity. In addition, the hologram generated by each single metasurface can uniquely identify its shareholder. Furthermore, we demonstrate that the inherent translational alignment sensitivity between two stacked metasurface holograms can be used for spatial multiplexing, which can be further extended to realize optical rulers.

Observing 0D subwavelength-localized modes at ~100 THz protected by weak topology - Lu, Jinlong; Wirth, Konstantin G.; Gao, Wenlong; Heßler, Andreas; Sain, Basudeb; Taubner, Thomas; Zentgraf, Thomas (Science Advances)
Topological photonic crystals (TPhCs) provide robust manipulation of light with built-in immunity to fabrication tolerances and disorder. Recently, it was shown that TPhCs based on weak topology with a dislocation inherit this robustness and further host topologically protected lower-dimensional localized modes. However, TPhCs with weak topology at optical frequencies have not been demonstrated so far. Here, we use scattering-type scanning near-field optical microscopy to verify mid-bandgap zero-dimensional light localization close to 100 THz in a TPhC with nontrivial Zak phase and an edge dislocation. We show that because of the weak topology, differently extended dislocation centers induce similarly strong light localization. The experimental results are supported by full-field simulations. Along with the underlying fundamental physics, our results lay a foundation for the application of TPhCs based on weak topology in active topological nanophotonics, and nonlinear and quantum optic integrated devices because of their strong and robust light localization.

A dielectric metasurface optical chip for the generation of cold atoms - Zhu, Lingxiao; Liu, Xuan; Sain, Basudeb; Wang, Mengyao; Schlickriede, Christian; Tang, Yutao; Deng, Junhong; Li, Kingfai; Yang, Jun; Holynski, Michael; Zhang, Shuang; Zentgraf, Thomas; et al. (Science Advances)
Compact and robust cold atom sources are increasingly important for quantum research, especially for transferring cutting-edge quantum science into practical applications. In this study, we report on a novel scheme that uses a metasurface optical chip to replace the conventional bulky optical elements used to produce a cold atomic ensemble with a single incident laser beam, which is split by the metasurface into multiple beams of the desired polarization states. Atom numbers ~10 7 and temperatures (about 35 μK) of relevance to quantum sensing are achieved in a compact and robust fashion. Our work highlights the substantial progress toward fully integrated cold atom quantum devices by exploiting metasurface optical chips, which may have great potential in quantum sensing, quantum computing, and other areas.

Energy transfer within the hydrogen bonding network of water following resonant terahertz excitation - Elgabarty, Hossam; Kampfrath, Tobias; Bonthuis, Douwe Jan; Balos, Vasileios; Kaliannan, Naveen Kumar; Loche, Philip; Netz, Roland R.; Wolf, Martin; Kühne, Thomas; Sajadi, Mohsen (Science Advances)
Energy flow in the hydrogen bonding network of water is traced by resonant terahertz excitation and off-resonant optical probing.
Keywords: Multidisciplinary

Nonlinear integrated quantum electro-optic circuits - Luo, Kai-Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Science Advances)
An integrated chip with quantum state generation, active polarization manipulation, and precise time control is demonstrated.
Keywords: Multidisciplinary

Probing measurement-induced effects in quantum walks via recurrence - Nitsche, Thomas; Barkhofen, Sonja; Kruse, Regina; Sansoni, Linda; Štefaňák, Martin; Gábris, Aurél; Potoček, Václav; Kiss, Tamás; Jex, Igor; Silberhorn, Christine (Science Advances)

Single-pixel computational ghost imaging with helicity-dependent metasurface hologram - Liu, Hong-Chao; Yang, Biao; Guo, Qinghua; Shi, Jinhui; Guan, Chunying; Zheng, Guoxing; Mühlenbernd, Holger; Li, Guixin; Zentgraf, Thomas; Zhang, Shuang (Science Advances)